"Hello World!" Gwenpool: Marvel's Camusian absurd hero. Issue 3 (3rd May 2020) - Paylor, A. J.
ABSTRACT: Existentialism and comic books have a long association. Existentialist themes within comic books have often been identified and explored by scholars. Such examinations have, however, generally neglected the ideas of Albert Camus. This is perhaps surprising given the popularity of superhero comic books and the fact that one of Camus's most famous works examines what constitutes an existentialist, absurd, hero. This article seeks to redress this relative neglect. The intention of this article is to demonstrate that the Marvel Comics character Gwenpool embodies the qualities which Camus prescribed to an absurd hero in his philosophical essay 'The Myth of Sisyphus.' To achieve this, this article examines Gwenpool's awareness of what Camus describes as the absurd. That is to say, Gwenpool's recognition of the antinomy which exists between her desire to live a meaningful life and the meaninglessness of the universe she inhabits. This article then examines Gwenpool's rejection of two possible responses to the "absurd": suicide and philosophical suicide. Following this, Gwenpool's adherence to the third response to the absurd which Camus outlines, and the only response of which he approves, is explored: revolt.